Heat rejection design for zero liquid discharge Shand coal-fired power station integrated with CO2 capture and storage. (March 2019) - Srisang, Wayuta; Sanpasertparnich, Teerawat; Quagraine, Emmanuel; Bruce, Corwyn; Giannaris, Stavroula; Janowczyk, Dominika; Jacobs, Brent
Highlights: Design of a hybrid heat rejection system for Shand Power Station to maintain Zero Liquid Discharge while integrating CO2 capture and storage. Evaluation of the effect of annual variations in dry bulb and wet bulb temperatures on the heat load by using Thermoflex. The yearly average power consumption of the hybrid system was calculated and compared with those of the design case. Abstract: The integration of CCS to a coal-fired power plant not only results in the increase in water consumption and cooling duty, but also additional water discharge especially from cooling the flue gas to the much lower temperature required for the CO2 capture process. This paper presents the design of a heat rejection system for the Shand Power Station that maintains a neutral liquid impact on the existing plant while adding SO2 and CO2 capture processes. Moreover, the effect of temperatures throughout the year on heat rejection load and power consumption is investigated. The heat rejection systems were designed and optimized by using Aspen HYSYS and Aspen EDR to accommodate 245 MWth which is the additional heat rejection required for the CO2 capture process, assuming that flue gas pre-cooling is accomplished from an external source. In the case of this study, the flue gas cooler heat integration, and a quench system serviced by cooling duty which is offset from the existing unit condenser due to the integration steam source provides the required flue gas pre-cooling. The hybrid heat rejection system, which uses a dry cooler in series with a wet cooler, cools the CO2 capture plants circulating water loop from 44.5 °C to 25 °C. The wet cooling is by a Wet Surface Air Cooler (WSAC), in order to provide a second layer of protection to ensure that none of the CO2 capture chemicals will be inadvertently released to the environment. The design dry bulb and wet bulb temperatures are based on the 85 percentiles of the Estevan's weather data for 26 years from 1991 to 2017, and are 18 °C and 13.7 °C respectively. Water produced by the capture process was utilized as the primary source for the wet cooling in order to avoid increasing the overall water draw of the facility. Using the dry cooler for rejecting the higher grade heat, and the WSAC for the lower grade heat improves cooling water temperature, while also maintaining Zero Liquid Discharge (ZLD) status. The heat load on the dry cooling and wet cooling is 156.5 and 81.8 MWth which corresponds to 67 and 33% of the total heat respectively. The effect of annual variations in dry bulb and wet bulb temperatures on the heat load of the hybrid cooling system was investigated by using Thermoflex. It was noted that the annual average heat rejection load shifted toward wet cooling system due to the lower temperature and the need to evaporate water available from the CO2 capture process with the percentage of 58% for dry cooling and 42% for wet cooling. This resulted in reduction of fan power requirements. The average fan power consumption throughout a year is 2.58 MW which is only 52% of the design case (4.96 MW).